2015
DOI: 10.1007/s10865-015-9617-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of physical activity on sleep: a meta-analytic review

Abstract: A significant body of research has investigated the effects of physical activity on sleep, yet this research has not been systematically aggregated in over a decade. As a result, the magnitude and moderators of these effects are unclear. This meta-analytical review examines the effects of acute and regular exercise on sleep, incorporating a range of outcome and moderator variables. PubMed and PsycINFO were used to identify 66 studies for inclusion in the analysis that were published through May 2013. Analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

66
669
20
19

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 902 publications
(832 citation statements)
references
References 123 publications
66
669
20
19
Order By: Relevance
“…Similar to previous intervention studies (28), a moderate effect of EI on sleep quality was found in both ITT and PP analyses. Effects on sleep quality were maintained at follow-up.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar to previous intervention studies (28), a moderate effect of EI on sleep quality was found in both ITT and PP analyses. Effects on sleep quality were maintained at follow-up.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, we aimed to investigate the effect of exercise on five secondary outcomes of employee well-being: self-efficacy, sleep, work ability, cognitive functioning, and aerobic fitness. Prior work shows that fatigued employees often show deficiencies in these outcomes (20)(21)(22)(23)(24), while it has been suggested that exercise positively affects them (25)(26)(27)(28)(29), see 30 for a more extensive justification for the choice of secondary outcomes). We therefore expected that exercise improves general and work-related self-efficacy, sleep quality and quantity, work ability, cognitive functioning, and aerobic fitness.…”
mentioning
confidence: 99%
“…It was suggested in a study that exercise can even improve the sleep latency, but no change was observed for other sleep indices, such as sleep duration, sleep efficiency, sleep disturbance, and daytime functioning (Yang, Ho, Chen, & Chien, 2012). Another meta-analysis on the effect of exercise on sleep quality, including 66 studies, demonstrated positive effects of the exercise in this field (Kredlow, Capozzoli, Hearon, Calkins, & Otto, 2015). Kamath et al (2014) argued that sleep duration influences on the metabolism and regulates body weight which is consistent with our study, demonstrating the correlation between BMI and sleep quality, sleep latency, sleep disturbance, sleep medications.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to research on adults [19], a minimal intensity threshold may exist in order for exercise to elicit an effect on adolescent sleep stage characteristics. This may be in part due to the slower accumulation of sleep pressure amongst adolescents [63], with only high-intensity exercise resulting in changes to SWS proportions due to depletions in brain energy stores [111].…”
Section: Effects Of Exercise On Sleepmentioning
confidence: 93%
“…While there has been several reviews on the effects of sleep on academic and cognitive outcomes in adolescents [8,[11][12][13], the need for exercise and physical activity amongst adolescents [10,[14][15][16], and the influence of exercise on sleep amongst adults [17][18][19], there has not been a review integrating these topics, specifically looking into the impact of sleep loss, and the sleep promoting effects of exercise in adolescents.…”
Section: Introductionmentioning
confidence: 99%